Pengaruh Literasi Keuangan dan Sikap Berutang Terhadap Keputusan Keuangan Nasabah Gadai PT. Pegadaian Kanwil VI Makassar Cabang Pelita A - Amelia; La Ode Sumail; Rezki Arianty Akob (Insan Cita Bongaya Research Journal, 2022)
This study aims to examine the effect of Financial Literacy and Debt Behavior on Finance Decisions pawn customers PT. Pegadaian Kanwil VI Makassar Pelita Branch. The population in this study consisted of 4.023 respondents and the sampling was carried out using the non-probability sampling method. The sample used is 98 respondents. The analytical tool used is multiple linear regression analysis which aims to re-examine the Effect of Financial Literacy and Debt Behavior on Finance Decisions pawn customers PT. Pegadaian Kanwil VI Makassar Pelita Branch by using the Statistical Package for the Social Sciences Vers. 25. The results of this study indicate that partially the financial literacy variable has a positive and significant effect on financial decisions, debt behavior does not have a significant effect on financial decisions.